Diversity of Butterfly Species of the Superfamily Papilionoideae in Two Types of Garden Habitats in the Tea and Quinine Research Center Area, Pasir Jambu District, Bandung Regency, West Java - Parsaoran, Abraham William; Putra, Adhiya Nabhan Kusuma; Putri, Jihan Nadhila; Amirah, Karina Mutiara; Naca, Syiraaz Banafsaj; Ruslan, Hasni (Universitas Nasional Jakarta, 2024)
Indonesia is one of the countries with the second highest biodiversity in the world, known as a megabiodiversity country. One of the highest biodiversity in Indonesia is butterflies, which belong to the order Lepidoptera. Butterflies have significant ecological value in ecosystems, acting as pollinators, environmental bioindicators, and ecosystem balancers. This research was conducted from May 1-5, 2024, in the Tea and Quinine Research Center Area, Pasir Jambu District, Bandung Regency, West Java. Butterfly observations were made in the morning from 08.00 to 12.00 WIB and in the afternoon from 13.00 to 16.00 in two types of gardens, namely tea gardens and coffee gardens. The data collection method used was the exploration method. Measurements of abiotic factors at the observation locations, including temperature, humidity, wind speed, and light intensity, showed differences in the two locations. In the observation locations, a total of 49 species and 366 individuals of butterflies were found. The similarity index of butterflies in the two habitat types was 57%. The butterfly diversity index in this study was 2.6 for the tea garden and 2.53 for the coffee garden. The Hutchinson test results showed no significant difference between the two habitats. The species evenness index in the tea garden was 0.74 and in the coffee garden was 0.73. The dominance index of butterflies in the two habitats was 0.2 for the coffee garden and 0.14 for the tea garden. The butterfly species with the highest number of individuals in the tea and coffee garden habitats were Ypthima pandocus and Delias belisama. The protected butterfly species found in the research location was Troides amphrysus.